Analysis of Slang Words Formation Found in the Lyrics of Drake’s Songs - I Gede Budasi; I Putu Abdi Bhuwana (k@ta: A Biannual Publication on the Study of Languange and Literature, 2020)
This research attempted to find out the word formation processes of slang words found in the lyrics of Drake’s songs. This research applied descriptive qualitative research design. The theory of the 18 word formation processes based on the synthesized theories from Yule (2010), Mattielo (2008), O’Grady, Aronoff, & Dobrovolsky (1997) were used as guidelines. This study found out that there were 190 slang words existing in the lyrics of the songs. They were respectively categorized into clipping (27%), coinage (25%), multiple process (22%), compounding (18%), reduplicatives (2%), variation (2%), borrowing (1%), blending (1%), acronym and initialism (1%), reversed forms (0.5%), and onomatopoeia (0.5%).